To solve the recurrence relation:
an + an-1 = 3n^2 , where a0 = 0, using generating functions, we can follow these steps:
- Define the generating function A(x) for the sequence {an} as follows:
A(x) = a0 + a1x + a2x^2 + a3x^3 + …
- Multiply the recurrence relation by x^n and sum over all n≥1:
∑(an + an-1)x^n = ∑3n^2 x^n
- Simplify the left-hand side using the shift property of the summation:
∑anx^n + ∑an-1x^n = ∑3n^2 x^n
∑anx^n + x ∑an-1x^(n-1) = ∑3n^2 x^n
- Replace ∑anx^n by A(x) and use the identity ∑anx^n = xA(x) – a0:
A(x) + xA(x) – a0 = ∑3n^2 x^n / (1-x)
- Replace the sum on the right-hand side by its generating function:
A(x) + xA(x) – a0 = 3x^2 / (1-x)^3
- Solve for A(x):
A(x) = 3x^2 / [(1-x)^3 (1+x)]
- Use partial fraction decomposition to write A(x) in a more manageable form:
A(x) = A1/(1-x) + A2/(1-x)^2 + A3/(1-x)^3 + A4/(1+x)
where A1 = 1, A2 = 2, A3 = 2, and A4 = -2.
- Expand each term using the binomial series:
A(x) = 1 + 2x + 3x^2 + 4x^3 + …
- Finally, read off the coefficients to get the solution to the original recurrence relation:
an = n(n+1).